Pelatihan Pembuatan Media Pembelajaran Interakif Bagi Guru Smb Mahabodhicitta Desa Sampetan Dengan Menggunakan Smart App Creator - Joko Adi Pradana; Evi Sefriani Dwika; Partono Nyanasuryanadi; Cindi Agustina (Departement of Mathematics Education, 2023)
Buddhist Sunday School, as a form of non-formal religious education, aims to instill saddha/sraddha and bhakti to continuously enhance the faith of the Buddhist community (PP 55 of 2007). In the pursuit of this objective, the use of instructional media is crucial in the teaching and learning process. The underutilization of technology as a teaching aid in Sunday Schools has drawn the researcher's attention, prompting an intention to provide training on creating interactive instructional media using the Smart App Creator. The training method involves pre-training assessment, the actual training, and training evaluation conducted for the teachers of Buddhist Sunday School (BSS) in Sampetan Village. This training is meant to be incorporated into the curriculum of Mahabodhicitta Buddhist Sunday School in Sampetan Village. With the implementation of the Smart App Creator, the teachers of Mahabodhicitta BSS and its students will experience a new way of learning and teaching techniques during Sunday School classes. Through this training, the BSS teachers will be equipped to develop android-based mobile learning instructional media, resulting in an improvement of their pedagogical abilities.